The relationship between self-esteem and the online environment in preadolescents - Călin, Mariana Floricica; Sandu, Mihaela Luminița; Robu, Ruxandra Elena (Technium Social Sciences Journal, 2022)
Self-esteem is a widely studied concept in the field of psychology and not only,this human component according to the multitudes of researches carried out ends up affecting a wide spectrum of activities carried out by people if they are in an imbalance. I chose this staging of preadolescence in relation to self-esteem and the online environment because I consider this period the most susceptible to changes caused by the environment, regardless of what that may be and especially in the virtual environment where today's preadolescents have found either a confidant, an emotional support, a satisfactory of needs or even a refuge. This new environment that in the last 15 years has developed amazingly, and which was meant to make our lives easier and bring us only satisfaction, has also proven to bring dissatisfaction in the most unexpected aspects of developing human life. Another reason why I chose this research topic also comes from personal experience during adolescence, at the beginning of this stage getting acquainted with social media and facing different states or changes of perspective now realizing in adulthood as being at that time flawed for my development, I understood that what was created in my mind and later in my behavior was influenced by the new digital environment to which I had adhered without to think that I will expose myself at the same time to such an influential space.